Mouse models of human chromosomal translocations and approaches to cancer therapy. - Rabbitts, T; Appert, A; Chung, G; Collins, E; Drynan, L; Forster, A; Lobato, M; McCormack, M; Pannell, R; Spandidos, A; Stocks, MR; Tanaka, T; et al. (2001)
Cancer arises because of genetic changes in somatic cells, eventually giving rise to overt malignancy. Principle among genetic changes found in tumor cells are chromosomal translocations which give rise to fusion genes or enforced oncogene expression. These mutations are tumor-specific and result in production of tumor-specific mRNAs and proteins and are attractive targets for therapy. Also, in acute leukemias, many of these molecules are transcription regulators which involve cell-type-specific complexes, offering an alternative therapy via interfering with protein-protein interaction. We are studying these various features of tumor cells to evaluate new therapeutic methods. We describe a mouse model of de novo chromosomal translocations using the Cre-loxP system in which interchromosomal recombination occurs between the Mll and Af9 genes. We are also developing other in vivo methods designed, like the Cre-loxP system, to emulate the effects of these chromosomal abnormalities in human tumors. In addition, we describe new technologies to facilitate the intracellular targeting of fusion mRNAs and proteins resulting from such chromosomal translocations. These include a masked antisense RNA method with the ability to discriminate between closely related RNA targets and the selection and use of intracellular antibodies to bind to target proteins in vivo and cause cell death. These approaches should also be adaptable to targeting point mutations or to differentially expressed tumor-associated proteins. We hope to develop therapeutic approaches for use in cancer therapy after testing their efficacy in our mouse models of human cancer.